Socio-religious and pastoral research - Marzal, Manuel M. (1972)
There is a question that I have heard several times from the lips of priests, they are concerned about the effectiveness of their current pastoral methods, not only because those methods were never very adapted for certain sectors (think, for example, of the different indigenous groups), but also because rapid changes in society and increasing secularization. Consequently, they fear that the divorce between the religiosity of the priests and of the more cultivated minorities and the religiosity of the majority will be accentuated, and thus they feel the urgency to do some religious research in their parishes to know the real situation.